How war begins dispatches from the Ukrainian invasion - Igort 1958- (Fantagraphics Books, Inc, 2024)
"In this real-time work of graphic journalism (posted serially on Facebook), the cartoonist Igort uses the medium of comics to depict the telephone testimonies of Ukrainians as Russia invaded in 2022. In vignettes that grow ever more horrifying -- infiltrating spies, bombed cities, recorded accounts of children whose parents were murdered in front of their eyes, and more -- Igort also relays the events that led up to the invasion, such as the torture and killing of human rights activists. He tells stories of individual struggle and suffering with no resolutions because they are still happening: Of Tetiana, who fled in the middle of the night with her children and whose car broke down on the steppe. And Maksim, who lived in Belgium and went for a five-day family visit and who could not return home when his mother died of COVID due to martial law. In art styles that veer from cartoon simplicity to photorealism, depending on what the moment demands, Igort paints portraits and scenes of ordinary people trying to survive among almost 10,000 civilian deaths. How War Begins is an important document of the past, the present, and the future"--
Chiefly illustrations
Keywords: Geschichte 2022; Russisch-Ukrainischer Krieg; Ukraine; Russian Invasion of Ukraine, 2022 / Comic books, strips, etc; Ukraine / History / Russian Invasion, 2022- / Comic books, strips, etc; Ukraine / History / 1991- / Comic books, strips, etc; Nonfiction comics; Comics journalism; Comics (Graphic works); Graphic novels; War comics; Biographies; Bandes dessinées autres que de fiction; Bandes dessinées; Bandes dessinées de guerre; Bandes dessinées de reportage; Comic